Signs of convergence in party policies on digital technologies. A comparative analysis of party policy stances in Ireland and Germany. Issue 2 (3rd April 2019) - König, Pascal D.
ABSTRACT: Industrialized countries face comparable societal and economic changes induced by advances in digital technologies. Are these similar developments filtered through the country-specific economic and socio-cultural context, thus leading to different policy stances of party-political actors? This question is probed looking at Germany and Ireland as two West European countries with highly different conditions. Drawing on party manifestos for the three most recent elections in the examined countries, the analysis maps parties' policy priorities in a common space. Instead of persisting differences in policy stances related to digital technologies, there is a clear trend of convergence between 2007 and 2017. Despite the very different country settings, parties in both countries, particularly in Germany, have shifted towards putting greater emphasis on aspects of productivity and efficiency. The findings suggest that adaptive pressures and the economic importance of digital technologies prevail over political-economic and socio-cultural country differences in shaping political actors' policy priorities.